Removal of Grey BL from Dye Wastewater by Derris (Pongamia Glabra) Leaf Powder by Adsorption - T. Mugugan; A. Ganapathi; R. Valliappan (E-Journal of Chemistry)
The dye, Grey BL was adsorbed on an adsorbent prepared from mature leaves of the Pungan tree (Pongamia glabra). A batch adsorption study was carried out with variable adsorbate concentration, adsorbent amount and pH. Ninety three percent of the dye could be removed by 2 g of the derris leaf powder from 1 L of an aqueous solution containing 25 mg of the dye at 300 K. The adsorption followed pseudo first order kinetics with a mean rate constant of 3.73 ×10-3 min-1 and an intraparticle diffusion rate constant of 6.36 x10-2 mg g-1 min-0.5. A possible mechanism of adsorption was suggested on the basis of concurrently operating surface adsorption and pore diffusion. The experimental data yielded excellent fits with Langmuir and Freundlich isotherm equations. The Langmuir monolayer capacity had a mean value of 8.27 mg g-1. The results indicated that the dye, Grey BL, strongly interacts with a biomass-based adsorbent, the Derris (Pongamia glabra) leaf powder.